Analyse de l’effet de la concurrence végétale sur la croissance de l’Iroko (Milicia excelsa) en forêt dense tropicale perturbée de l’Est–Cameroun - L. Mbonayem; K.S. Bobo (VertigO, 2018)
The simulation currently made on commercial species regarding the determination of their minimum diameter of management by the method of calculating the rate of recovery and which allows them to reach the minimum exploitable diameter after the rotation ignores ecological factors species growth (soil nutrients, water accessibility, competition due to the presence of other species, climate change ...). This research undertakes to reflect on Iroko growth variations based on competitive interactions related to the presence of the surrounding population. This study was conducted in disturbed heterogeneous population in the dense forest of the Congo Basin and can serve as a starting point for developing an approach to identifying the role of each environmental factor in the growth process of the species in heterogeneous forest and useful for future development of allometric growth patterns of tropical species.